The impact of player transfers on european football clubs stock prices : an event study analysis - Garcia, Maria Teresa (2024)
This paper examines how player transfers influence the stock prices of publicly traded football clubs through an event study approach. The analysis focus on five prominent European teams—Manchester United, Juventus, Borussia Dortmund, Olympique Lyon, and Ajax—focusing on 230 player transactions that occurred between 2018 and 2023. The study assesses abnormal returns (AR) and cumulative abnormal returns (CAR) within a 10-day event window, encompassing five days prior to and following the announcements of transfers. Findings indicate that high-value transfers typically result in positive abnormal returns, which reflect investor optimism regarding the new player's potential impact on the team's success. In contrast, sales and loans of players tend to elicit negative reactions from the market, indicating concerns about possible adverse effects on team performance. These results support the Efficient Market Hypothesis by demonstrating that stock prices quickly adjust to new information such as player transfers. This research adds to the expanding literature at the intersection of sports events and financial markets, providing valuable insights for clubs operating in capital markets and investors aiming to understand the dynamics of football markets.